Mycorrhizal Fungal Diversity and Community Composition in Two Closely Related Platanthera (Orchidaceae) Species. - Fabiana Esposito; Hans Jacquemyn; Michael Waud; Daniel Tyteca (PLoS ONE)
While it is generally acknowledged that orchid species rely on mycorrhizal fungi for completion of their life cycle, little is yet known about how mycorrhizal fungal diversity and community composition vary within and between closely related orchid taxa. In this study, we used 454 amplicon pyrosequencing to investigate variation in mycorrhizal communities between pure (allopatric) and mixed (sympatric) populations of two closely related Platanthera species (Platanthera bifolia and P. chlorantha) and putative hybrids. Consistent with previous research, the two species primarily associated primarily with members of the Ceratobasidiaceae and, to a lesser extent, with members of the Sebacinales and Tulasnellaceae. In addition, a large number of ectomycorrhizal fungi belonging to various families were observed. Although a considerable number of mycorrhizal fungi were common to both species, the fungal communities were significantly different between the two species. Individuals with intermediate morphology showed communities similar to P. bifolia, confirming previous results based on the genetic architecture and fragrance composition that putative hybrids essentially belonged to one of the parental species (P. bifolia). Differences in mycorrhizal communities between species were smaller in mixed populations than between pure populations, suggesting that variation in mycorrhizal communities was largely controlled by local environmental conditions. The small differences in mycorrhizal communities in mixed populations suggests that mycorrhizal fungi are most likely not directly involved in maintaining species boundaries between the two Platanthera species. However, seed germination experiments are needed to unambiguously assess the contribution of mycorrhizal divergence to reproductive isolation.